The impact of using divergent thinking strategies on reading comprehension - A. Al Masri; T. Krishan; F. Al Talahin; S. Almassarweh (Образование и наука)
Introduction. Divergent thinking strategies are based on brain activity represented by a series of successive and branching questions related to a particular reading text. These strategies stimulate the minds of sixth graders to think of new stimuli such as finding a solution to a specific problem, or making a specific judgment, or predicting future events, which produces new and innovative solutions and achieves a deeper understanding of the target reading text.The present research aims to investigate the impact of divergent thinking strategies in developing reading comprehension skills among sixth-grade students in the English language.Methodology and research methods. The authors used the quasi-experimental approach. A pre-post design was used to identify the effect of employing divergent thinking strategies in developing reading comprehension skills. The study sample consisted of 136 students, who were selected purposefully and distributed into two groups: experimental and control groups. Students in experimental group were taught using divergent thinking strategies. Students in control group were taught in the usual way.Results and scientific novelty. The analysis of covariance (ANCOVA) found statistically significant differences between the two groups in favour of the experimental group in achievement. In addition, significant differences were found in the Motivation for Learning English between the two groups. It was found that divergent thinking strategies stimulate students’ thinking through various questions and allow them to look at their familiar knowledge with a new vision, to produce and generate new ideas with creative features.Practical significance. The current study is useful in determining the appropriate reading comprehension skills for students, and targeting them in developing these skills. This research also draws the attention of teachers to the importance of including strategies compatible with the brain, including divergent thinking strategies, when planning reading lessons. As for the educational supervisors, it puts in their hand’s strategies based on the theory of learning in the brain, including the divergent thinking strategies and how to employ them in reading lessons in order to develop reading comprehension. Moreover, these research materials can be employed by mentors in directing teachers to depart from the framework of traditional methods through the use of divergent thinking strategies in their classroom teaching practices.